HUBUNGAN ANTARA KOMPETENSI PEDAGOGIK GURU DENGAN EFEKTIVITAS PEMBELAJARAN PENDIDIKANJASMANI, OLAHRAGA, DAN KESEHATAN (STUDI PADA GURU PEGAWAI NEGERI SIPIL SEKOLAH DASAR NEGERI SE-KECAMATAN TAMAN KABUPATEN SIDOARJO TAHUN 2013) - SETYORINI, (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Pedagogical competence is a typical competence which only belong to teachers, thus differentiate their professions from the others. Physical education pedagogical competence of teachers is the teacher’s ability to manage the learning, including the students understanding, instructional design and implementation, learning outcome evaluation, and the development of student’s potential. Pedagogical competence of teachers plays important role in learning process done by the teacher in order for the whole process considered to be qualified. The quality of learning demonstrated by the effectiveness of learning that can be observed from preparation, execution, and the student’s activities during learning process. Besides, it can be revealed by knowing the results of four components which are results, volition, method, and cooperation. Therefore, it is necessary to know the relation between pedagogical competence with the effectiveness of learning, and how much the contribution of pedagogical competence to the effectiveness of pedagogical learning. This research is non-experimental with the type of correlation with the quantitative descriptive approach. The research subjects are 34 physical education teachers as PNS in a public elementary schools in Taman, Sidoarjo. Pedagogical competence of teachers are determined by the pedagogical assessment questionnaires filled out by 30 principals. While the effectiveness of learning is determined by class formative evaluation (FCE) questionnaire completed by 1,334 students and analyzing classroom observation radio and filling a physical education evaluation sheet by 5 observers. The hypothesis is proven using Pearson product moment formula r and r Spearman rank order. The results showed that the value of teacher’s pedagogical competence is in category great with a value of 82.88%. While the effectiveness of learning physical FCE based questionnaire in category good with a value of 2.68 and based on the analysis of instructional videos in category good with a value of 68.35%. From the results of hypothesis testing there is a significant relationship between teacher’s pedagogical competence with physical education learning effectiveness FCE based questionnaire. Proved by the value of rcount 0.402>0.399 rtable. While based on the video analysis shows that there is no significant relation proved by the p value 0.097 > 0.05 with rcount equal to 0.277 in the category of weak ties. The relation between teacher’s pedagogical competence with learning effectiveness of physical education based on FCE questionnaire is 16.16% and based on analysis of video learning using physical education classroom observation sheet of 5.16%. Conclusion: so the better the effectiveness of pedagogical competence, the better teacher’s physical education learning will become. Keywords: Pedagogical Competence, Learning Effectiveness